Watch out, psychoanalysis is everywhere! Parker, I (1997) Psychoanalytic culture: Psychoanalytic discourse in Western society. London: Sage Publications. ISBN 0-7619-5643-3 pbk. 290 pages. - Hayes, Grahame (PINS-Psychology in Society, 2026)
Freud is reputed to have said to Jung on their journey to the USA - Freud had been invited by Stanley Clark to lecture at Stanford University - that little did they (the Americans) know it, but they (he and Jung - psychoanalysts) were bringing them the plague. Freud's well-known sarcasm and cynicism were often prescient in ways he would have been surprised by. Maybe the metaphor for today would more appropriately be "nuclear fallout", "radioactivity", not because I think psychoanalysis is this lethal or potent, but because it is everywhere and yet we can't see it, smell it, or even hear it! This in part seems to be 'What Ian Parker is suggesting about psychoanalysis's insertion into the cultural discourse of western society. It is a case of: "Watch out, psychoanalysis is everywhere!"